New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata) - Hirose, M.; Gordon, D.p.; D’hondt, J.-L. (Zootaxa, 2020)
The status of seriated Amathia species (Bryozoa: Ctenostomata) in Japan is reviewed. Several historical specimens and materials recently collected from several localities along the Japanese coast are examined in this study. Amathia acervata Lamouroux, 1824, collected from Japan by Wilhelm Gottlieb Tilesius in 1804, was examined and is redescribed from a reconstituted fragment of the sole type specimen. Material previously reported from Wakayama Prefecture is very similar to Amathia acervata, but differs in having fewer autozooid pairs per cluster, which spiral in different directions; the species is described as a new species Amathia brevisilva n. sp. Measurements of colony characters vary according to the effects of fixation, but stolon length, the ratio of autozooid clusters on stolons, spirality and pigmentation are useful characters for the identification of Japanese seriated Amathia. In addition, two new species are described, Amathia reptopinnata n. sp. and Amathia fimbria n. sp. Amathia reptopinnata n. sp. is characterized by its robust form, dark colour, dichotomous branching, long stolons, long autozooidal clusters and pinnately arranged prostrate zooids. Amathia fimbria n. sp. was found only in the Showa Emperor collection, and is characterized by its compact colony form, remarkably short internode length and trichotomous branching.